(untitled) (Veterinária Notícias, 2020)
American Tegumentary Leishmaniasis (ATL) is a widely distributed anthropozoonosis caused by the protozoa Leishmania spp. and is considered a serious public health problem. We aimed to assess Manhuaçu’s burden caused by ATL through the profiling of all ATL case reports during the period from 2010 to 2015. A descriptive, ecological and retrospective study of the confirmed cases of ATL was carried out using data regarding the age, sex, area of residence, type of entry (new case or recurrence), and clinical form of the disease of the existing registered reports provided by the Sistema de Informação de Agravos de Notificação (SINAN). We observed that the first quarter of the years showed higher number of reports. The 58 notifications were classified as a first time occurrence, being 95% of the cutaneous form of the disease, and 76% of the cases in male patients. Regarding the location of the infection, 86% of the patients belonged to the rural area, and most (60%) were between 20 and 59 years old. Thus, the epidemiological profile of infections of ATL in Manhuaçu, MG indicates that male individuals aged between 20 and 59 years old and living in rural areas are more likely to get infected. Moreover, it is important to know the epidemiological profile of ATL cases for adequate health surveillance and prevention of the disease on this region.